The occurrence of cold waves in Rio Grande do Sul at the end of the 18th century and in the 19th century and the production of climatological knowledge - Galarça, Paulo Jolar Pazzini (Khronos, 2024)
The state of Rio Grande do Sul experienced intense cold at the end of the 15th century and heavy snowfalls in the 19th century, specifically in 1858, 1862, 1867, 1870, 1871, 1873, 1875, 1879 and 1885. Due to the social problems caused by these severe weather events, the need arose to create a meteorological service. There were several initiatives in the 19th century, most notably the service organized by the Commissão de Obras do Porto de Rio Grande, the Public Works station in Porto Alegre and the Escola de Artes e Officio station in Pelotas.